PERCEPTION OF SOCIAL MEDIA MARKETING BY USERS OF E-COMMERCE MARKETPLACE AND ONLINE FOOD DELIVERY - Yoesoep Edhie Rachmad (Universitas Kristen Indonesia Toraja, 2022)
Social commerce is growing rapidly in Indonesia because of the ease of use of social media applications. The online shopping feature on social media has caused some e-commerce users to start switching to using social media for shopping. Several social media now provide paid features and shopping features such as Instagram Shop, Facebook Shop, and TikTok Shop. This is part of social commerce which has the basic function of social media with a trading function. Qualitative methods are used in this study. The object of this study was 200 users, namely three online food delivery e-commerce users, social media users, and e-commerce marketplace users. The purpose of this research is to analyze perceptions about social media marketing by e-commerce online food delivery users, social media users, and e-commerce marketplace users. The findings of the study were (1) 200 respondents always looked for information and product reviews on social media before shopping on e-commerce marketplaces and social media. (2) Social media is a business opportunity for influencer marketing and selebgram in the influencer industry. (3) Social media has the potential to become a promising buying and selling platform in the future, and has a great opportunity to become social commerce.